2014
DOI: 10.2217/whe.14.47
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Stroke in Women with Risk Factor Management: Blood Pressure and Cholesterol

Abstract: actorStroke is a major cause of death and disability in adults worldwide. Prevention focused on modifiable risk factors, such as hypertension and hyperlipidemia, has shown them to be of significant importance in decreasing the risk of stroke. Multiple studies have brought to light the differences between men and women with regards to stroke and these risk factors. Women have a higher prevalence of stroke, mortality and disability and it has been shown that preventive and treatment options are not as comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Moreover, adequate blood pressure reduction, cessation of cigarette smoking and the use of antithrombotic therapy in atrial fibrillation are the most effective modifiable RFs in stroke prevention 24 . Among the women, RFs in this study are similar to those found in other studies [25][26] . However, researchers mention that unlike Causians, large-vessel thrombosis, cerebral venous thrombosis, and cardioembolism are common among young Asian women with stroke 27 .…”
Section: Type Of Stroke and Other Rfssupporting
confidence: 91%
“…Moreover, adequate blood pressure reduction, cessation of cigarette smoking and the use of antithrombotic therapy in atrial fibrillation are the most effective modifiable RFs in stroke prevention 24 . Among the women, RFs in this study are similar to those found in other studies [25][26] . However, researchers mention that unlike Causians, large-vessel thrombosis, cerebral venous thrombosis, and cardioembolism are common among young Asian women with stroke 27 .…”
Section: Type Of Stroke and Other Rfssupporting
confidence: 91%
“…Women over 80 have higher mortality and poorer functional outcomes compared to age-matched men after stroke. Previous studies have reported that women have a longer life expectancy than men, and that women are 4–6 years older than men at the onset of stroke, which may account for their higher disability rate and poorer prognosis ( 9 , 10 ). TIA prevalence rates vary, depending on the age distribution of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that differences between men and women in the extent of improvement are partly explained by women in some countries being more sensitive to health information, having better health seeking behaviour, and having better access to primary prevention. [34, 35] An alternative explanation is that neuro-vascular risk factors are more frequent and severe in men and have declined faster in women, for example tobacco. [36, 37]…”
Section: Discussionmentioning
confidence: 99%